2003
DOI: 10.1021/ol034903j
|View full text |Cite
|
Sign up to set email alerts
|

Simple One-Flask Method for the Preparation of Hydroxamic Acids

Abstract: [reaction: see text] A one-step conversion of carboxylic acids to hydroxamic acids under very mild conditions is described. This simple and efficient method has been applied for the synthesis of enantiopure hydroxamate of alpha-amino acids and peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…[17] Under these conditions, the reaction of 1 with O-benzyl-hydroxylamine resulted in the isolation of 2 in good yields (Scheme 4, procedure a). A further improvement in the reaction of 1 to 2 was achieved by using ethylchloroformiate as activating agent (Scheme 4, procedure b).…”
Section: Resultsmentioning
confidence: 99%
“…[17] Under these conditions, the reaction of 1 with O-benzyl-hydroxylamine resulted in the isolation of 2 in good yields (Scheme 4, procedure a). A further improvement in the reaction of 1 to 2 was achieved by using ethylchloroformiate as activating agent (Scheme 4, procedure b).…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1-12 have been reported elsewhere [31][32][33][34][35][36][37][38][39][40][41][42] using different procedures to those described here.…”
Section: Hydroxamic Acid Synthesesmentioning
confidence: 99%
“…[46] Variations of these methods have been reported and are summarised in a recent paper that describes a simple onepot method for the syntheses of hydroxamic acids in high yields. [47] The formation of hydroxamic acids and bioactive hydroxamate-containing compounds in both solution and solid phase has also recently been the subject of a comprehensive review by Lou et al [48] Two possible hydroxamic acid tautomers exist ( Figure 5); the keto tautomer, which is predominant under acidic conditions, and the enol form, which is more stable in alkaline media. [49] Furthermore, NMR spectroscopic studies have shown that each tautomer can exist as (E) and (Z) isomers ( Figure 5), further extending their structural diversity.…”
Section: Syntheses and Structuresmentioning
confidence: 99%